2016
DOI: 10.1016/j.jsps.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A review on the strategies for oral delivery of proteins and peptides and their clinical perspectives

Abstract: In the modern world, a number of therapeutic proteins such as vaccines, antigens, and hormones are being developed utilizing different sophisticated biotechnological techniques like recombinant DNA technology and protein purification. However, the major glitches in the optimal utilization of therapeutic proteins and peptides by the oral route are their extensive hepatic first-pass metabolism, degradation in the gastrointestinal tract (presence of enzymes and pH-dependent factors), large molecular size and poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
127
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(135 citation statements)
references
References 118 publications
0
127
0
1
Order By: Relevance
“…If insulin is to be absorbed in the small intestine, it must survive the stomach and conditions in the small intestine. 13 Fortunately, a number of pH sensitive materials have been recently developed that are capable of protecting insulin from the environment of the stomach and selectively releasing insulin when encountering the neutral pH conditions of the small intestine. 14 Currently, this leaves insulin’s low absorption in the small intestine (Figure 1B) as the major barrier standing in the way of developing oral insulin.…”
mentioning
confidence: 99%
“…If insulin is to be absorbed in the small intestine, it must survive the stomach and conditions in the small intestine. 13 Fortunately, a number of pH sensitive materials have been recently developed that are capable of protecting insulin from the environment of the stomach and selectively releasing insulin when encountering the neutral pH conditions of the small intestine. 14 Currently, this leaves insulin’s low absorption in the small intestine (Figure 1B) as the major barrier standing in the way of developing oral insulin.…”
mentioning
confidence: 99%
“…Some of the most exposed problems in several reviews are related to permeation [5,13,20,110]. The physicochemical properties of sensitive molecules and conditions of absorption of FP systems have also limited their function [111,112].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other results have showed that FP nano carriers can reduce the transepithelial resistance [60]; therefore, their potential use for clinical applications is still uncertain [20]. Consequently, some FP systems still cannot be used in oral formats due to their low efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful oral protein formulation in the future can also utilize the smart polymeric nanoparticles which can protect and target the proteins to the specific site and release when required [6,7].…”
mentioning
confidence: 99%